2003
DOI: 10.1074/jbc.m300525200
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Agonists Have Different Efficacy Profiles for G Protein Activation, Rapid Desensitization, and Endocytosis of Mu-opioid Receptors

Abstract: The differential ability of various -opioid receptor (MOP) agonists to induce rapid receptor desensitization and endocytosis of MOP could arise simply from differences in their efficacy to activate G proteins or, alternatively, be due to differential capacity for activation of other signaling processes. We used AtT20 cells stably expressing a low density of FLAG-tagged MOP to compare the efficacies of a range of agonists to 1) activate G proteins using inhibition of calcium channel currents (I Ca ) as a report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
179
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(191 citation statements)
references
References 65 publications
10
179
2
Order By: Relevance
“…16 The potency and efficacy of the opioid agonists correlate well with previous studies in AtT-20 cells and with studies in native neurons where activation of GIRK channels or inhibition of I Ca was used to determine agonist intrinsic activity. 11,[18][19][20] The data we obtained with the hyperpolarization assay are similar to what we obtained when we measured MOR Figure 5. Treatment of AtT-20 µ-opioid receptor (MOR) cells with nigericin, a K-selective antibiotic ionophore, caused a greater decrease in fluorescent signal than the maximally effective concentration of DAMGO (p < 0.05).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…16 The potency and efficacy of the opioid agonists correlate well with previous studies in AtT-20 cells and with studies in native neurons where activation of GIRK channels or inhibition of I Ca was used to determine agonist intrinsic activity. 11,[18][19][20] The data we obtained with the hyperpolarization assay are similar to what we obtained when we measured MOR Figure 5. Treatment of AtT-20 µ-opioid receptor (MOR) cells with nigericin, a K-selective antibiotic ionophore, caused a greater decrease in fluorescent signal than the maximally effective concentration of DAMGO (p < 0.05).…”
Section: Discussionsupporting
confidence: 74%
“…Many studies have reported the endomorphins as being partial agonists, 18,21 whereas methadone has been reported to be an agonist with a similar efficacy to DAMGO. 11,22,23 The most likely explanation for the discrepancy in our study is that methadone appeared to have a reduced maximal effect because of its propensity to block K channels, including the GIRK channels likely to contribute to the hyperpolarization measured in the present study. 22,24 Conversely, the observation that the maximum effect of the endomorphins was similar to that of well-recognized high-efficacy agonists suggests the presence of some spare receptors in our system, as noted previously with similar cell lines.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…When compared with other mu agonists, morphine induces less internalization of the mu opioid receptor (Borgland et al, 2003;McPherson et al, 2010;Zheng et al, 2011). This suggests that the prototypical role of b-arrestin 2 in initiating receptor internalization does not explain how the effects of morphine, but not of other mu agonists, are altered in mice lacking b-arrestin 2.…”
Section: Discussionmentioning
confidence: 64%